Dynamics of Inflation, Economic Growth, Money Supply and Exchange Rate in India: Evidence from Multivariate Analysis - Behera, Jaganath (Quarterly Journal of Econometrics Research, 2017)
The present study investigates the dynamics of inflation, GDP and exchange rate and money supply in India for the period 1975-2012. The data source is cumulated from the Reserve Bank of India (RBI) Handbook of Statistics 2012. The empirical findings of the study show that there is a long-run equilibrium relationship exist among the variables. The result also suggest that money supply has a positive effect on GDP growth in India. The result of error correction indicates that correct and negative sign for Gross Domestic Product and exchange rate. The behavior of GDP implies there is no problem of adjustment in the long run in case of shocks in the short run. The VECM Granger causality confirms that unidirectional causality from GDP to inflation and exchange rate to inflation. The result also found that exchange rate Granger causes both GDP and money supply at 10 percent level of significance. The impulse response result shows that GDP has a positive response to money supply from the occurrence to the end of the period. Whereas the response of exchange rate to money supply negative in the whole lag period. The variance decomposition result explainss that no significant part of variance is caused by money supply. The result also reveals that cyclical variance of GDP caused by money supply, exchange rate, and inflation.